KUALITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM UWE LINO KABUPATEN DONGGALA - Witdyaningsih, Witdyaningsih (Katalogis, 2018)
The purpose of this study is to find out How Quality Services Regional Uwe Lino Water Company District Donggala. Types of data used are primary data and secondary data. The Data collection techniques is done through observation, interviews, documentation. Informants using purposive sampling technique for the employees and for the community accidental. Informants in this study as many as five (5) persons. Analysis of the data used that model of Miles and Huberman, namely data reduction, data presentation, and conclusion. The theory used is the theory of Parasuraman in Zeithami. Quality of service Regional Uwe Lino Water Company District Donggala still not good. This in the know of all five aspects have direct evidence (Tangibles) namely infrastructure inadequate, realibility, service is provided is less precise and faster time to handle the service interruption. Responsiveness is employer responses were very slow in dealing with customer complaints interference experienced by PDAM Uwe Lino Costumers. Assurance is namely that employees PDAM Uwe Lino District Donggala already showed his polite and friendly in serving the community. Emphaty is said to be less well. Because the service is not yet fully in accordance with what is expected by the customer.